Assessment of thermal comfort indices in an open air-conditioned stadium in hot and arid environment. (August 2021) - Ghani, Saud; Mahgoub, Ahmed Osama; Bakochristou, Foteini; ElBialy, Esmail A.
Abstract: Thermal comfort indices are vital tools when assessing outdoor thermal comfort in hot and arid environments. Selecting a representative thermal comfort index for outdoor environments is challenging. This paper presents a comparative study of the suitability of seven different thermal comfort indices, namely PMV, discomfort index, cooling power index, Humidex, WBGT, SET, and UTCI in assessing outdoor thermal comfort. The thermal comfort indices were compared to the thermal sensation vote (TSV) obtained from a thermal comfort questionnaire of spectators seated in a semi-open air-conditioned stadium. Seated in six different zones, a total of 532 spectators participated in an online questionnaire. The results of the survey indicated high levels of climate acceptability, with small variations among the stadium zones and between genders. Almost 40% of the spectators reported feeling '' cool '', while 28% of the spectators were feeling ' 'slightly cool'' and 21% reported a '' neutral '' thermal perception. Hence, CFD simulations were used to predict the values of the seven thermal comfort indices. The thermal comfort indices' values, obtained from the CFD simulations, were compared to their counterparts obtained from the questionnaire. The WBGT index showed good agreement to the actual questionnaire data with an average difference of 8.8%. The other six indices yielded an average range of difference of (15%–46%). The WBGT index deemed the most suitable to assess outdoor thermal comfort for hot and arid regions, followed by the UTCI and the SET indices, with average differences of 14% and 15%, respectively. The CPI index deemed not suitable for hot and arid regions compared to other indices. Graphical abstract: Image 1